Modulation of Presynaptic GABA Release by Oxidative Stress in Mechanically-isolated Rat Cerebral Cortical Neurons - Hahm, Eu-Teum; Seo, Jung-Woo; Hur, Jinyoung; Cho, Young-Wuk (The Korean journal of physiology & pharmacology, 2010)
Reactive oxygen species (ROS), which include hydrogen peroxide (H(2)O(2)), the superoxide anion (O(2) (-).), and the hydroxyl radical (OH.), are generated as by-products of oxidative metabolism in cells. The cerebral cortex has been found to be particularly vulnerable to production of ROS associated with conditions such as ischemia-reperfusion, Parkinson's disease, and aging. To investigate the effect of ROS on inhibitory GABAergic synaptic transmission, we examined the electrophysiological mechanisms of the modulatory effect of H(2)O(2) on GABAergic miniature inhibitory postsynaptic current (mIPSCs) in mechanically isolated rat cerebral cortical neurons retaining intact synaptic boutons. The membrane potential was voltage-clamped at -60 mV and mIPSCs were recorded and analyzed. Superfusion of 1-mM H(2)O(2) gradually potentiated mIPSCs. This potentiating effect of H(2)O(2) was blocked by the pretreatment with either 10,000-unit/mL catalase or 300-microM N-acetyl-cysteine. The potentiating effect of H(2)O(2) was occluded by an adenylate cyclase activator, forskolin, and was blocked by a protein kinase A inhibitor, N-(2-[p-bromocinnamylamino] ethyl)-5-isoquinolinesulfonamide hydrochloride. This study indicates that oxidative stress may potentiate presynaptic GABA release through the mechanism of cAMP-dependent protein kinase A (PKA)-dependent pathways, which may result in the inhibition of the cerebral cortex neuronal activity.